(untitled) (PANGEEA, 2025)
Sustainable development of tourism in Sibiu County. The central idea underlying sustainable development is the preservation of biodiversity and cultural heritage for future generations. Lester Brown rightly states that: “we do not inherit the earth from our parents but we borrow it from our children”.